Consumption pattern of meat and meat products in and around Nagpur city of Maharashtra - Mundhe , B L; Rathod, K S; Badhe , S R; Roupesh , G (Journal of Meat Science, 2023)
A study was conducted to understand consumption patterns and factors influencing consumption pattern of meat and meat products in and around Nagpur city. A proportionate random sampling method was used to conduct a survey (sample size of 400) using a bilingual (Marathi and English) questionnaire comprising questions related to the socioeconomic particulars of the consumers, meat and meat products consumption patterns, and factors influencing on it. The study revealed that most respondents were 15 to 30 years (52.5%) and college graduates (35.8%). About 43% of the respondents reported a family income of more than six lakhs. Most of the consumers ate meat for taste (54.4%) and health benefits (27.0%) and responded that they usually consume meat once a week (50.3%). The most preferred meat in and around Nagpur city was poultry meat (50.8%), followed by chevon (27.5%) and Fish & seafood (18.7%). Most respondents (66.8%) were unwilling to pay more for lean meat. The results indicated that most respondents consider safety, nutritional value, taste, market price, availability, and children’s meat preference as essential factors influencing meat consumption.
Keywords: Socioeconomic; meat Consumption; factors; consumers; Questionnair